PERANAN KREDIT USAHA RAKYAT TERHADAP LABA PADA UMKM KERIPIK MANGLENG DI DESA BUKIT BARISAN CURUP - Aulia, Nanda; Meriana, Meriana; Afriansyah, Berlian; Paddery, Paddery (Politeknik Raflesia Press, 2023)
This study was to determine the role of People's Business Credit on Profit at MSMEs Mangleng Chips Ms. Rika in Bukit Barisan Village and to determine the impact felt by MSME actors from the funds obtained from KUR. This study used quantitative data with primary data sources and secondary data sources. While the data collection method is the method of observation, interviews, documentation, and internet research. This analysis uses the growth ratio analysis method. The research data shows that there is no decrease in income. It is known that the role of KUR has an impact on the development of MSMEs in Bukit Barisan Village with economic growth of 49.82725% of income before using KUR. the results of the analysis of income growth (Growth) showed a positive growth in the income of MSMEs with mangleng chips in the village of Bukit Barisan as much as 49.82725%. The increase in income by a round of 50% can be said to be almost a part of the initial increase from entrepreneurs. The researcher sees the use of people's business loans as an opportunity to increase their business quite realistically. Keywords: People's Business Credit, Profit, MSME